Characteristics of hearing loss in patients with herpes zoster oticus. Issue 46 (November 2016) - Kim, Chang-Hee; Choi, Hyerang; Shin, Jung Eun
Abstract : Abstract: Patients with herpes zoster oticus (HZO) may commonly show symptoms associated with 7th and 8th cranial nerve (CN VII and CN VIII) dysfunction. The aim of this study is to investigate the characteristics of hearing loss in patients with HZO and discuss possible mechanisms. Ninety-five HZO patients who showed at least one of the symptoms of CN VII and CN VIII dysfunction between January 2007 and October 2014 were included in this study. Hearing loss was defined when the mean thresholds of pure tone audiometry (PTA) in speech frequency (0.5 kHz + 1 kHz + 2 kHz/3) or isolated high frequency (4 kHz + 8 kHz/2) were greater than 10 dB in the affected ear compared with the healthy ear, and a total of 72 patients were classified as the hearing loss group. The difference of mean PTA thresholds between affected and healthy ears was significantly greater in the high frequency range than in low range (20.0 ± 11.5 dB vs. 12.9 ± 15.7 dB, P = 0.0026) in patients with hearing loss ( n = 72). The difference between affected and healthy ear was significantly greater in patients with vertigo ( n = 34) than those without vertigo ( n = 38) in both the high ( P = 0.033) and low ( P = 0.024) frequency ranges. In contrast, the differences between affected and healthy ears were not significantly different between patients with facial palsy ( n = 50) and those without facial palsy ( n = 22) in both the high ( P = 0.921) and low ( P = 0.382) frequency ranges. In patients with HZO, hearing loss is more severe in the high frequency range than in the low frequency range. Hearing impairment is more severe in patients with vertigo than in those without vertigo in both the high and low frequency ranges, even though the degree of hearing impairment is not significantly different between patients with and without facial palsy. These findings indicate that the mechanisms of viral spread from CN VII to CN VIII may differ between vestibular and audiologic deficits.